An evaluation of vendor managed inventory practices from small and medium indian enterprises - Shen, Lixin; Govindan, Kannan; Borade, Atul B.; Diabat, Ali; Kannan, Devika (Journal of Business Economics and Management, 2013)
Vendor managed inventory has proven to be an effective tool for improving the supply chain performance by decreasing inventory-related costs and increasing customer service. It is quite evident from the literature that vendor managed inventory (VMI) has been successfully implemented in small and medium enterprises (SMEs). However, studies related to the implementation of VMI in Indian SMEs are very limited. Therefore, this study presents an empirical investigation of VMI practices in Indian SMEs using survey methodology. The paper evaluates the benefits, barriers, and effects of adopting VMI in Indian SMEs, and also investigates the IT tools and software used for VMI adoption. Furthermore, this study explores the dissimilarities among various sectors of SMEs adopting VMI. Based on the proposed methodology, it is found that organizational issues and unwillingness to share information are the major barriers. In terms of benefits, the major influencing variables are improved efficiency and improved channel relations.